Understanding News Researchers through a Content Analysis of Dissertations and Theses - Feeney, Mary (Qualitative and Quantitative Methods in Libraries; Vol 3 No 1 (2014): March 2014 Issue, 2017)
Understanding the information needs of researchers is an important role of academic libraries. This paper describes the methodology and results of a research study that explored the use of newspapers by scholars in different disciplines through a content analysis of dissertations and theses. The purpose of the study was to examine which disciplines utilize newspapers, whether U.S. or non-U.S. newspapers are used more frequently, and whether researchers typically consult historical or current newspapers for their research. Results indicate that scholars in a wide range of disciplines utilize newspapers in their research. Analysis of the time periods used by disciplines and the origin of newspapers used in research is included